2018 International Olympic Committee Consensus Statement on Prevention, Diagnosis, and Management of Pediatric Anterior Cruciate Ligament Injuries. Issue 3 (16th March 2018) - ,; Ardern, Clare L.; Ekås, Guri; Grindem, Hege; Moksnes, Håvard; Anderson, Allen F.; Chotel, Franck; Cohen, Moises; Forssblad, Magnus; Ganley, Theodore J.; Feller, Julian A.; Karlsson, Jón; et al.
In October 2017, the International Olympic Committee hosted an international expert group of physical therapists and orthopaedic surgeons who specialize in treating and researching pediatric anterior cruciate ligament (ACL) injuries. The purpose of this meeting was to provide a comprehensive, evidence-informed summary to support the clinician and help children with ACL injury and their parents/guardians make the best possible decisions. Representatives from the following societies attended: American Orthopaedic Society for Sports Medicine; European Paediatric Orthopaedic Society; European Society for Sports Traumatology, Knee Surgery, and Arthroscopy; International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine; Pediatric Orthopaedic Society of North America; and Sociedad Latinoamericana de Artroscopia, Rodilla, y Deporte. Physical therapists and orthopaedic surgeons with clinical and research experience in the field and an ethics expert with substantial experience in the area of sports injuries also participated. This consensus statement addresses 6 fundamental clinical questions regarding the prevention, diagnosis, and management of pediatric ACL injuries. Injury management is challenging in the current landscape of clinical uncertainty and limited scientific knowledge. Injury management decisions also occur against the backdrop of the complexity of shared decision making with children and the potential long-term ramifications of the injury.